Edukasi dalam upaya Menekan Kasus Perceraian melalui Pendidikan Agama Islam di Dusun Dasan Lendang Desa Kerumut - Muh. Tarmizi Tahir; Alwan, Muhammad; Mashun, Mashun; Sri Harmonika; Sunardi, Sunardi (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The problems that are the basis for divorce in the Dasang Lendang hamlet are caused by quarrels, economic problems, failure to fulfill the elements of kafa'ah in marriage, online shopping that causes debt, online gambling. So this Community Service aims to increase the optimization of religious knowledge in reducing divorce cases in the Dasan Lendang hamlet community, Kerumut Village. This Community Service activity uses the Participatory Action Research (PAR) approach. The method used in this service is Socialization. The results of the service show that providing understanding and knowledge to the community is carried out with a socialization strategy from students and lecturers by providing lectures, counseling and marriage advice to the community. So that the community is aware of the dangers of things such as a) Quarrels, b) economic problems, c) online shopping addiction. the above factors have the potential to cause household problems and trigger divorce. So that the implications for the community are expected to be active in participating in educational activities through the majlis taklim held in the prayer room and in the mosque and lectures by the tuan guru to deepen their knowledge of religion.